Apakah yang Mempengaruhi Minat Menggunakan QRIS pada Masyarakat Gen-Z? - Kadek Rizpa Dwi Anggayasa; M. Rudi Irwansyah (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the factors that influence the interest in using QRIS as a digital payment system among Gen-Z individuals in Buleleng Regency, as well as to determine the most dominant factor. The research employs a quantitative approach using factor analysis. Data were collected through questionnaires distributed to 150 Gen-Z respondents residing in Buleleng Regency who had used QRIS at least twice. The results of the analysis reveal that from four main indicators: trust, perceived ease of use, security, and perceived usefulness, one primary factor was formed, referred to as the perception of system reliability. This factor has an eigenvalue of 3.067 and explains 76.675 percent of the variance, indicating a significant contribution to the interest in using QRIS, thus making it the most dominant factor. These findings suggest that Gen-Z evaluates digital payment services holistically based on the reliability of the technology and is more inclined to use systems that are perceived as trustworthy, efficient, secure, and beneficial.